PENGARUH FUNGSI KOMUNITAS BELAJAR DAN PEMBUATAN AKSI NYATA DI PLATFORM MERDEKA MENGAJAR TERHADAP KOMPETENSI PROFESIONAL GURU SD NEGERI SE KECAMATAN TEMANGGUNG - Eko Ujiandayani; Yovitha Juliejantiningsih; Maryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT Teacher professional competence is very necessary in the world of education, so that we are not left behind by the dynamics of the times. Factors that can improve teacher professionalism are the implementation of learning communities and also the creation of real actions on the independent teaching platform. The objectives of this research are 1) To determine the influence of the function of the learning community on teacher professional competence. 2) To determine the effect of creating real actions on the independent teaching platform on teachers' professional competence. 3) To determine the influence of the function of the learning community and the creation of real action on the independent teaching platform on the professional competence of State Elementary School teachers in Temanggung District. This research uses a quantitative approach. The sampling technique, namely proportionate random sampling, obtained a sample of 127 teachers consisting of school principals and teachers from 23 state elementary schools in Temanggung District, Temanggung Regency. Data collection uses a questionnaire. Data analysis techniques start from descriptive statistics then prerequisite tests after that are multiple linear regression tests. The results of the research show (1) There is an influence of the function of the learning community on the professional competence of State Elementary School teachers in Temanggung District, this is based on the calculated f value of 155.305 > f-table 3.92 with a Sig value of 0.000 < 0.05. (2) There is an influence of making real actions on the independent teaching platform on the professional competence of State Elementary School teachers in Temanggung District, this is based on the calculated f value of 141.650 > f-table 3.92 and the Sig value of 0.000 < 0.05. (3) There is an influence of the function of the learning community and the creation of real action on the independent teaching platform on the professional competence of State Elementary School teachers in Temanggung District, this is based on the calculated f value of 102.224 > -table 3.07 and the Sig value of 0.000 < 0.05. Suggestions: (1) For teachers, this research can provide input and policy in an effort to draw decisions regarding appropriate platforms and training models. (2) school principals can achieve continuous improvement in teacher professional competence by providing full support, motivation and providing facilities to utilize the independent teaching platform. (3) this research can be used as a source of data and reference for further research based on more complete information. Keyword: Learning communities, creating real action, teacher professional competence.